The effect of escalation of commitment and project risk in resources allocation decision - Astrid Febriana Loru Ngara Ledewara; Intiyas Utami (Jurnal Akuntansi dan Auditing Indonesia, 2019)
This research aims to examine the causal relationship between escalation of commitment and project risk with decision making in resource allocation (production cost). In this research the allocation of resources is in determining the cost of direct labor and material costs. To trigger cognitive dissonance, the determination of higher labor costs will increase the bonus of individuals working as production managers. When kos production has been set in a certain number, labor costs are high, while factory overhead costs is fixed, cause material costs to be low. The lower the material cost, the lower the product quality. Escalation of commitment is a condition when individuals already know the potential risks in the future, but still take risks for their decisions. This study proposes that the production cost allocation decision in conditions of high commitment escalation will tend to choose decisions that benefit themselves compared to when the escalation of commitment is low (choosing a labor cost allocation is higher than the material cost). This research also predicts that individuals in the face of high-risk projects will tend to allocate resources that benefit themselves. In addition, the interaction of the existence of a low level of escalation of commitment and a low risk project level will reduce the allocation of production costs to direct labor costs. This research uses a laboratory experiment design with 102 accounting students at a private university in Central Java who act as production managers with paper and pencil test. This experiment uses a 2x2 between subject. The results of the research show that there is a causal relationship between the escalation of commitment and the allocation of human resources and there is a causal relationship between the escalation of commitment and project risk. This finding also shows that there is an interaction between escalation of commitment, project risk and resource allocation decisions.